Tutankhamun knew the names of the two great gods : d̲t and nḥḥ as fundamental concepts of pharaonic ideology - Gregory, Steven R. W., (Archaeopress Egyptology ;, 2022)
'Tutankhamun Knew the Names of the Two Great Gods' offers a new interpretation of the terms Dt and nHH as fundamental concepts of Pharaonic ideology, terms that, until now, have often been treated as synonyms reflecting notions related to the vastness of time.